1990
DOI: 10.1073/pnas.87.6.2284
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and structural motifs of chicken gizzard myosin light chain kinase.

Abstract: The amino acid sequence for chicken smooth muscle myosin light chain kinase (smMLCK) was deduced from a full-length cDNA. This has allowed dermition ofboth the complete sequence of the inactive 64-kDa proteolytic fragment, which contains the pseudosubstrate autoregulatory sequence, and of the active 61-kDa Ca2+/calmodulin-independent fragment, which lacks the autoregulatory domain. Comparison of the two sequences shows that the autoregulatory domain extends from Asn-780 to Arg-808. The peptide Leu-774 to Ser-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
123
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(125 citation statements)
references
References 23 publications
1
123
0
1
Order By: Relevance
“…Many CaM regulated kinases, including skMLCK, smMLCK, and MKII, are activated by the removal of an autoinhibitory sequence from the active site of the enzyme, an event that can be triggered either by the binding of CaM to a nearby sequence or by phosphorylation of key residues (Zurini et al, 1984;Edelman et al, 1985;Pearson et al, 1988;Olson et al, 1990;Gallagher et al, 1993;Brickey et al, 1994;Krueger et al, 1995;Goldberg et al, 1996). For these proteins, the smaller Ca2+ affinity enhancement observed for the full-size enzyme relative to the isolated target peptide is likely to stem, at least in part, from the energetic cost of removing autoinhibition.…”
Section: Origins Of the Different Tuning Observed For Target Peptidesmentioning
confidence: 99%
“…Many CaM regulated kinases, including skMLCK, smMLCK, and MKII, are activated by the removal of an autoinhibitory sequence from the active site of the enzyme, an event that can be triggered either by the binding of CaM to a nearby sequence or by phosphorylation of key residues (Zurini et al, 1984;Edelman et al, 1985;Pearson et al, 1988;Olson et al, 1990;Gallagher et al, 1993;Brickey et al, 1994;Krueger et al, 1995;Goldberg et al, 1996). For these proteins, the smaller Ca2+ affinity enhancement observed for the full-size enzyme relative to the isolated target peptide is likely to stem, at least in part, from the energetic cost of removing autoinhibition.…”
Section: Origins Of the Different Tuning Observed For Target Peptidesmentioning
confidence: 99%
“…In the central portion of the molecule, the sequences commonly observed in various protein kinases [3][4][5] are found and, therefore, it is assigned that the catalytic domain exists at the central part of the molecule. Calmodulin binding peptide was isolated by Lukas et al [6] and the sequence correlates with residues 797-816 of chicken gizzard MLCK sequence [3,4] which lies towards the C-terminal side of the catalytic domain. Kemp et al [7] found that residues 788-811 showed significant homology to the N-terminal sequence of the regulatory light chain of myosin and that a synthetic peptide analog of this region inhibited Ca2÷/calmodulindependent MLCK activity.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of the regulatory light chain of myosin is catalyzed by a Ca~-*/ calmodulin-dependent myosin light chain kinase (MLCK). The structure-function relationships of smooth muscle MLCK are greatly assisted by the determination of the complete amino acid sequence [3][4][5]. In the central portion of the molecule, the sequences commonly observed in various protein kinases [3][4][5] are found and, therefore, it is assigned that the catalytic domain exists at the central part of the molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 It is generally accepted that this initial phase is dependent on phosphorylation of the 20-kDa myosin light chain (MLC 20 ) and the consequent activation of the acto-myosin ATPase, with recruitment of fast-cycling cross-bridges. The regulation of MLC 20 phosphorylation is therefore a key limiting event of shortening velocity. Net MLC 20 phosphorylation reflects the opposing enzyme activity of myosin light chain kinase (MLCK) and myosin light chain phosphatase, which phosphorylate and dephosphorylate MLC 20 , respectively.…”
Section: Introductionmentioning
confidence: 99%